Uptake of Risk-Reducing Surgeries in an International Real-World Cohort of Hispanic Women - Chavarri-Guerra, Y (2024)
PURPOSE Women with pathogenic variants (PVs) in breast cancer (BC) and ovarian cancer (OC) associated genes are candidates for cancer risk-reducing strategies. Limited information is available regarding risk-reducing surgeries (RRS) among Hispanics. The aim of this study was to describe the uptake of RRS in an international real-world experience of Hispanic women referred for genetic cancer risk assessment (GCRA) and to identify factors affecting uptake. METHODS Between July 1997 and December 2019, Hispanic women, living in the United States or in Latin America, enrolled in the Clinical Cancer Genomics Community Research Network registry were prospectively included. Demographic characteristics and data regarding RRS were obtained from chart reviews and patient-reported follow-up questionnaires. Median follow-up was 41 months. RESULTS Among 1,736 Hispanic women referred for GCRA, 27.2% women underwent risk-reducing mastectomy (RRM), 25.5% risk-reducing salpingo-oophorectomy (RRSO) and, 10.7% both surgeries. Among BRCA carriers, rates of RRM and RRSO were 47.6% and 56.7%, respectively. In the multivariate analyses, being a carrier of a BC susceptibility gene (odds ratio [OR], 3.44), personal history of BC (OR, 6.22), living in the US (OR, 3.90), age ≤50 years (OR, 1.68) and, family history of BC (OR, 1.56) were associated with a higher likelihood of undergoing RRM. Carrying an OC susceptibility gene (OR, 6.72) was associated with a higher likelihood of undergoing RRSO. CONCLUSION The rate of RRS among Hispanic women is suboptimal. PV carriers, women with personal history of cancer, and those with a family history of cancer were more likely to have RRS, with less uptake outside the US. Understanding personal and systemic factors influencing uptake may enable interventions to increase risk appropriate uptake of RRS.